Electromagnetic Wavefront Engineering by Switchable and Multifunctional Kirigami Metasurfaces - Yingying Wang; Yang Shi; Liangwei Li; Zhiyan Zhu; Muhan Liu; Xiangyu Jin; Haodong Li; Guobang Jiang; Jizhai Cui; Shaojie Ma; Qiong He; Lei Zhou; et al. (Nanomaterials)
Developing switchable and multifunctional metasurfaces is essential for high-integration photonics. However, most previous studies encountered challenges such as limited degrees of freedom, simple tuning of predefined functionality, and complicated control systems. Here, we develop a general strategy to construct switchable and multifunctional metasurfaces. Two spin-modulated wave-controls are enabled by the proposed high-efficiency metasurface, which is designed using both resonant and geometric phases. Furthermore, the switchable wavefront tailoring can also be achieved by flexibly altering the lattice constant and reforming the phase retardation of the metasurfaces based on the “rotating square” (RS) kirigami technique. As a proof of concept, a kirigami metasurface is designed that successfully demonstrates dynamic controls of three-channel beam steering. In addition, another kirigami metasurface is built for realizing tri-channel complex wavefront engineering, including straight beam focusing, tilted beam focusing, and anomalous reflection. By altering the polarization of input waves as well as transformation states, the functionality of the metadevice can be switched flexibly among three different channels. Microwave experiments show good agreement with full-wave simulations, clearly demonstrating the performance of the metadevices. This strategy exhibits advantages such as flexible control, low cost, and multiple and switchable functionalities, providing a new pathway for achieving switchable wavefront engineering.